Biopolymer of Chitosan from Fish Scales as Natural Coagulant for IronContaminated Groundwater Treatment - Irawan, Chairul; Nata, Iryanti Fatyasari; Putra, Meilana Dharma; Marisa, Rosmasari; Asnia, Mira; Arifin, Yulian Firmana (Chemical Engineering Department, Syiah Kuala University, Banda Aceh, Indonesia, 2018)
Chitosan, the de-acetylated chitin derivative, was evaluated for its ability to be used as a natural coagulant for Martapura groundwater treatment. This study is used chitosan derived from original fish scales of Kalimantan called Papuyu (Anabas testudineus) for the treatment of iron ion-containing Martapura groundwater through coagulation-flocculation method. The reduction efficiency of iron ion removed by coagulation-flocculation processes using chitosan from Papuyu fish scales is the primary evaluating parameter. The obtained chitosan have been characterized and analyzed by Fourier transforms infrared spectroscopy (FTIR), X-ray Fluroscence (XRF) and Scanning electron microscopy (SEM). Using of the chitosan from Papuyu fish scales as coagulant at neutral pH and room temperature led to decreasing the groundwater iron concentration become 3.43 mg/L (around 71% removal). The result was then compare to the coagulation-flocculation treatment using the commercial chitosan from shrimps shell (93% deacetylated). Moreover, its found the coagulation-flocculation treatment using the chitosan from fish scales as coagulant more favor than the commercial one.